Changes in use land of defense in the process of land reform in Ukraine - Melnichuk А. (Land Management, Cadastre and Land Monitoring, 2019)
The changes in the quantitative and qualitative state of use of defense lands in the period from 1990 to 2017 were researched. As a result, it became known that since 1990 the total area of defense lands has decreased by 59.7%, and from 2010 to 2017 by 0.4%. The lands of the Ministry of Defense in the category of defense lands constitute 339.8 thousand hectares or 84.9% of the total area, the Ministry of Internal Affairs - 11.8 thousand hectares or 2.9%, the National Guard - 10,0 thousand hectares or 2.5%, the State Committee for the Protection of the State Border of 6.8 thousand hectares or 1.7%, the Society for the Defense of Ukraine - 3.1 thousand hectares or 0.8%, other military formations - 10.7 thousand hectares or 2.7%. Significant changes in the land use of defense took place after the occupation of the Autonomous Republic of Crimea by Russia. In particular, the area of defense lands decreased to 362.2 thousand hectares or 9.5%. In the structure of the land use of defense the component of built-on sites varies from 0.6% to 26.2%. Established, that significant changes that took place in the land use of defense did not increase of ecological, economic and social security, and, consequently, the safety of the life of the population of Ukraine. Keywords. Land use of defense, land of defense, land and property relations.